Interaction between prostate cancer cells and prostate fibroblasts promotes accumulation and proteolytic processing of basement membrane proteins. Issue 9 (4th May 2020) - Ojalill, Marjaana; Virtanen, Noora; Rappu, Pekka; Siljamäki, Elina; Taimen, Pekka; Heino, Jyrki
Abstract: Background: Tumor microenvironment or stroma has the potency to regulate the behavior of malignant cells. Fibroblast‐like cells are abundant in tumor stroma and they are also responsible for the synthesis of many extracellular matrix components. Fibroblast‐cancer cell interplay can modify the functions of both cell types. Methods: We applied mass spectrometry and proteomics to unveil the matrisome in 3D spheroids formed by DU145 prostate cancer cells, PC3 prostate cancer cells, or prostate‐derived fibroblasts. Similarly, DU145/fibroblast and PC3/fibroblast coculture spheroids were also analyzed. Western blot analysis and immunofluorescence were used to confirm the presence of specific proteins in spheroids. Cancer dissemination was studied by utilizing "out of spheroids" migration and invasion assays. Results: In the spheroid model cancer cell‐fibroblast interplay caused remarkable changes in the extracellular matrix and accelerated the invasion of DU145 cells. Fibroblasts produced structural matrix proteins, growth factors, and matrix metalloproteinases. In cancer cell/fibroblast cocultures basement membrane components, including laminins (α3, α5, β2, and β3), heparan sulfate proteoglycan (HSPG2 gene product), and collagen XVIII accumulated in a prominent manner when compared with spheroids that contained fibroblasts or cancer cells only. Furthermore, collagen XVIII was intensively processed to different endostatin‐containing isoforms by cancer cell‐derived cathepsin L. Conclusions: Fibroblasts can promote carcinoma cell dissemination by several different mechanisms. Extracellular matrix and basement membrane proteins provide attachment sites for cell locomotion promoting adhesion receptors. Growth factors and metalloproteinases are known to accelerate cell invasion. In addition, cancer cell‐fibroblast interplay generates biologically active fragments of basement membrane proteins, such as endostatin.